ARABIC LANGUAGE AND SOLIDARITY: A SOCIOLINGUISTIC STUDY OF THE GAZA HASHTAG ON SOCIAL MEDIA X - Mufidah Fitriani; Doni Wahidul Akbar (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This study examines the role of Arabic in building solidarity on social media X through the hashtag #غزة. Social movements, identity representation, and media narratives have been widely researched, but little attention has been given to how Arabic functions as a medium for unity and empathy in the digital space. Arabic is not only used as a means of communication, but also as a medium for solidarity. This research was conducted using qualitative methods through a netnographic approach over eleven months (January-November 2025). Data was collected through observation, documentation, selection, and classification of posts using Arabic language related to Gaza. The analysis was carried out using Teun A. Van Dijk's critical discourse analysis model, which covers the dimensions of text, social cognition, and social context. The findings of the study show that Arabic manifests mechanical solidarity through religious collective consciousness and organic solidarity through role differentiation in humanitarian action. This study recommends the integration of humanistic values in Arabic language education so that learning is oriented towards social and moral awareness